The mind within the brain how we make decisions and how those decisions go wrong - Redish, A. David (Oxford : Oxford University Press, 2013)
"In The Mind within the Brain, David Redish brings together cutting edge research in psychology, robotics, economics, neuroscience, and the new fields of neuroeconomics and computational psychiatry, to offer a unified theory of human decision-making. Most importantly, Redish shows how vulnerabilities, or "failure-modes," in the decision-making system can lead to serious dysfunctions, such as irrational behavior, addictions, problem gambling, and PTSD. Told with verve and humor in an easily readable style, Redish makes these difficult concepts understandable. Ranging widely from the surprising roles of emotion, habit, and narrative in decision-making, to the larger philosophical questions of how mind and brain are related, what makes us human, the nature of morality, free will, and the conundrum of robotics and consciousness, The Mind within the Brain offers fresh insight into one of the most complex aspects of human behavior"--
Machine generated contents note: -- Decisions and the brain -- 1 What is a decision? -- 2 The tale of the thermostat -- 3 The definition of value -- 4 Value, euphoria, and the do-it-again signal -- 5 Risk and reward -- The decision-making system -- 6 Multiple Decision-making systems -- 7 Reflexes -- 8 Emotion and the Pavlovian action-selection system -- 9 Deliberation -- 10 The habits of our lives -- 11 Integrating Information -- 12 The stories we tell -- 13 Motivation -- 14 The tradeoff between exploration and exploitation -- 15 Self-control -- The brain with a mind of its own -- 16 The physical mind -- 17 Imagination -- 18 Addiction -- 19 Gambling and behavioral addictions -- 20 PTSD -- 21 Computational psychiatry -- The human condition -- 22 What makes us human? -- 23 The science of morality -- 24 The conundrum of robotics -- Epilogue -- Appendix -- A Information processing in neurons -- B Gleaning information from the brain -- C Content-addressable memory -- Bibliography.
Includes bibliographical references.
Description based on print version record.
Keywords: Decision making; PSYCHOLOGY -- Cognitive Psychology; SELF-HELP / Motivational & Inspirational; Electronic books